2007
DOI: 10.1620/tjem.211.339
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Fails to Modify Arterial Baroreflex Sensitivity in Ovariectomized Female Rats

Abstract: M. and KOHZUKI, M. Exercise Training Fails to Modify Arterial Baroreflex Sensitivity inOvariectomized Female Rats. Tohoku J. Exp. Med., 2007, 211 (4), 339-345 In men, exercise training attenuates age-related reduction in baroreflex sensitivity, which is related to cardiovascular health. It is unknown, however, if this holds true for post-menopausal women. We examined the effects of exercise training on baroreceptor-heart rate (HR) reflex sensitivity in ovariectomized (OVX) and sham-operated (SO) Wistar-Kyoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 52 publications
1
2
0
Order By: Relevance
“…Additionally, Minami et al reported that ovariectomized rats at 20 weeks of age showed impairment in both baroreflex components, which supports the results observed in the present study. However, we cannot discard a sex difference in cardiovascular control, but apparently the time of castration may have been an important influence on the observed impairment.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, Minami et al reported that ovariectomized rats at 20 weeks of age showed impairment in both baroreflex components, which supports the results observed in the present study. However, we cannot discard a sex difference in cardiovascular control, but apparently the time of castration may have been an important influence on the observed impairment.…”
Section: Discussionsupporting
confidence: 92%
“…The failure of Ex and combined treatment (Cap + Ex) on reducing BP could be related to an impaired baroreceptor reflex. Baroreceptors are the structures responsible for promoting compensatory bradycardia and reducing BP in response to physical activity, and there are reports indicating that baroreceptor reflex is impaired in hypoestrogenic rats . This issue can explain why the BP remained elevated in the Ex and combination (Cap + Ex) groups.…”
Section: Discussionmentioning
confidence: 99%
“…BRS is reduced in individuals with hypertension, coronary heart disease or congestive heart failure [28]. In addition, BRS is reduced with advancing age, even in healthy subjects [29, 30]. However, in women, postmenopausal hypertension is often associated with cardiovascular autonomic alterations, such as a predominance of sympathetic control of the heart rate and decreases in BRS [31], to a greater extent than in age-matched men [32].…”
Section: Mechanisms Responsible For Postmenopausal Hypertension and Rmentioning
confidence: 99%